Introduction. (7th January 2013) - Howell, Robert; Kostikova, Anna; Vasilyev, Vadim V.
Abstract This article introduces the papers from two video conferences recently held between philosophers at Moscow State University and the University at Albany, State University of New York. The overarching theme is philosophical progress in the past fifty years, but the conferences were designed also to illustrate the range of work now being done by American analytic philosophers and by Russian thinkers. The Albany essays focus on philosophy of science, philosophical logic, Kantian studies, applied ethics, and ethical and political theory. The Russian essays concern philosophy of culture, philosophy of mind, phenomenology, social philosophy, feminism, and postmodernism. This introductory essay notes similarities and differences that exist among American and Russian approaches to philosophy and the prospects for the convergence (or not) of these approaches. It also indicates ways in which contemporary Russian thinkers are striking out in new directions while seeking to recover those parts of their past that were silenced during much of the twentieth century.